Epilepsy at different ages—Etiologies in a Norwegian population. Issue 1 (21st December 2018) - Dahl‐Hansen, Eline; Koht, Jeanette; Syvertsen, Marte
Summary: The causes of epilepsy are age related, but confirmative data from population‐based studies are scarce. Our aim was to describe the typical causes of epilepsy in the different age groups of a defined population. The study was cross‐sectional, based on a review of all medical files containing a diagnostic code for epilepsy at Drammen Hospital from 1999‐2013. Drammen Hospital serves the population of Buskerud County, with 272 228 residents (as of January 1, 2014), including 1771 people with active epilepsy. This group of persons with active epilepsy was divided into different age groups with the causes of epilepsy mapped in each group. The proportion with unknown etiology ranged from 27% (age 5‐9) to 41% (age 10‐19). Structural‐metabolic epilepsy and perinatal insults were the leading causes of epilepsy in the age group 5‐9 (46%), whereas disturbances of brain development dominated in the youngest (23% in patients ≤4 years old). In the group comprising persons with epilepsy ≥60 years old, stroke was the most common cause of epilepsy (44%). Despite recent advances in research and technology, a large number of patients in all age groups (including the youngest) still have an unknown cause of epilepsy. We conclude that an effort must be made to improve the diagnostics for and understanding of the causes of epilepsy across all ages.